Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1111/j.1467-8535.2005.00487.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a laptop university: a case study

Abstract: Technology is integral to carrying out many types of business transactions and has become entwined in the very fabric of everyday life. In the educational environment-particularly higher education-technology is underutilised as a pedagogical tool and in many cases remains largely untapped. Winona State University and its laptop programme learned some valuable lessons from the marriage between the application of the Seven Principles of Good Practice in Undergraduate Education and technology. The transformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 6 publications
2
16
0
4
Order By: Relevance
“…First, the predominant method of data collection is the case study (Weaver, 2005;Weaver & Nilson, 2005;Hyden, 2005;Birrenkott, Birtrand & Bolt, 2005;Brown, 2005;Granberg & Witte, 2005;Ohland & Stephan, 2005;Pargas & Weaver, 2005;Stephens, 2005;McVay, Snyder & Graetz, 2005). While this approach offers guidance and advice on best practices for using laptops, the reliability and validity of the data have yet to be confirmed for the general population.…”
Section: Methodological Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the predominant method of data collection is the case study (Weaver, 2005;Weaver & Nilson, 2005;Hyden, 2005;Birrenkott, Birtrand & Bolt, 2005;Brown, 2005;Granberg & Witte, 2005;Ohland & Stephan, 2005;Pargas & Weaver, 2005;Stephens, 2005;McVay, Snyder & Graetz, 2005). While this approach offers guidance and advice on best practices for using laptops, the reliability and validity of the data have yet to be confirmed for the general population.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…Mitra and Steffensmeier (2000) found that students who used laptops preferred taking classes where they could use the computer. Despite the affinity for using the computer, student satisfaction is higher when students report using the laptops for academic purposes (McVay, Snyder & Graetz, 2005).A number of studies have reported that students believe that laptops make learning "easier" (Barak, et al, 2006;Mitra & Steffensmeier, 2000; Hyden, 2006;Weaver & Nilson, 2005). This may be an extension of the notion that modern students have grown up with technology, and the progression to having the "convenience of a personally configured computer [that] students naturally use it as a life tool" (Brown &Lauricella and Kay 153 Pettito, 2003, p. 27).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some educational institutes provide students and academics with portable technologies to be used for learning and teaching (Zelin and Baird 2002;Demb, Erickson, and Hawkins-Wilding 2004;McVay, Snyder, and Graetz 2005), as these devices are believed to offer portability, accessibility and convenience (Kukulska-Hulme, Evans, and Traxler 2005). In addition, as reported by Savill-Smith and Kent (2003) in their study on the use of palmtop computers, these devices are relatively inexpensive, provide access to information and promote the development of information literacy, collaborative learning and independent learning, all within the context of students' learning.…”
Section: Introductionmentioning
confidence: 99%
“…Successful implementation of a mobile computing initiative requires that administrators, technical staff members, and department faculty members support the initiative. 12 Professional development for faculty members 4,9 and their buy-in to the purpose and benefits of the initiative 13,14 are 2 of the most prominent issues to address. Without faculty members who are supportive of the initiative and/or who have been adequately trained on how to utilize mobile computing within the curriculum, the initiative will not reach its full potential.…”
Section: Introductionmentioning
confidence: 99%